The role of swearing in creating an online persona: The case of YouTuber PewDiePie. (August 2017) - Beers Fägersten, Kristy
Abstract: This article is an investigation of the use of English-language swear words by Swedish, non-native speaker PewDiePie in the context of self-recorded, Let's Play horror videos uploaded to the video-sharing website, YouTube. Situating PewDiePie within the greater media landscape to establish both his success and notoriety, this article addresses the local interpretation of the globalization of English and the use of English swear words in Swedish media. The practice of swearing in the gaming context is discussed, and swearing instances in a selection of three of PewDiePie's horror game videos are analyzed. The article puts forth the argument that the use of English swear words contributes to the performance of PewDiePie as a specific, online persona, one that is both in line with the context of video gaming and conducive to a para-social relationship, allowing PewDiePie to achieve the overall goals of communicating with his viewers as peers and reducing the social distance between them. The article concludes that PewDiePie's practice of social swearing not only simulates casual conversation between friends, but actively reduces social distance, creates the illusion of intimacy, and contributes to his unprecedented success on YouTube.